If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 44.91 = 9g + 3.69 Reorder the terms: 44.91 = 3.69 + 9g Solving 44.91 = 3.69 + 9g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-9g' to each side of the equation. 44.91 + -9g = 3.69 + 9g + -9g Combine like terms: 9g + -9g = 0 44.91 + -9g = 3.69 + 0 44.91 + -9g = 3.69 Add '-44.91' to each side of the equation. 44.91 + -44.91 + -9g = 3.69 + -44.91 Combine like terms: 44.91 + -44.91 = 0.00 0.00 + -9g = 3.69 + -44.91 -9g = 3.69 + -44.91 Combine like terms: 3.69 + -44.91 = -41.22 -9g = -41.22 Divide each side by '-9'. g = 4.58 Simplifying g = 4.58
| .15(10-x)+x=0.40(10) | | 45=d^2 | | 4t^2-5t-60=0 | | -35=-22-w | | 5x+20=9x-53 | | 49x^3-9x=0 | | 8x-8y=32 | | 2y-4(6)=-12 | | 0.5+3=x-2 | | 23=14-x | | .15(8-x)+x=0.40(8) | | (2+i)z-3+2i=0 | | Y^2+2.5y-9=0 | | 2x-y-4=13 | | (80x+60y)-(2x+30y)= | | -7(u+4)=-3u-16 | | 3x+x=y-18 | | 9x+4x+2=8x+3+4x | | -9=-6+x | | .10(8-x)+x=0.40(8) | | 12-2t=1-t | | -9=32x | | (4y+5)(6y-1)= | | 32-6x=12 | | 8v+2=12+3v | | 32-10x=12 | | 4(3x+6)=8(-6x-3) | | 0.45(19-x)+x=0.40(19) | | 3x^2+7x-28=2x^2-7x+4 | | 2t=5t-45 | | 4x+20=14x+-70 | | -21=-3x-4x |